Nanotechnology in cervical cancer immunotherapy: Therapeutic vaccines and adoptive cell therapy - Zhou, Xuyan; Lian, Haiying; Li, Hongpeng; Fan, Meiling; Xu, Wei; Jin, Ye (Frontiers in Pharmacology, 2022)
Immunotherapy is an emerging method for the treatment of cervical cancer and is more effective than surgery and radiotherapy, especially for recurrent cervical cancer. However, immunotherapy is limited by adverse effects in clinical practice. In recent years, nanotechnology has been widely used for tumor diagnosis, drug delivery, and targeted therapy. In the setting of cervical cancer, nanotechnology can be used to actively or passively target immunotherapeutic agents to tumor sites, thereby enhancing local drug delivery, reducing drug adverse effects, achieving immunomodulation, improving the tumor immune microenvironment, and optimizing treatment efficacy. In this review, we highlight the current status of therapeutic vaccines and adoptive cell therapy in cervical cancer immunotherapy, as well as the application of lipid carriers, polymeric nanoparticles, inorganic nanoparticles, and exosomes in this context.